The role of pedagogy and psychology in improving the methodology of teaching mathematics in general secondary schools on the basis of a competency-based approach - Babaeva Maxfuza Abduvaitovna (Zien Journals, 2022)
In this article, the role of pedagogy and psychology in improving the methodology of teaching mathematics in general secondary schools on the basis of a competency-based approach to comprehensive competencies is covered. to solve tasks willingly and, most importantly, to enjoy the work he has done - the problem of developing life skills such as independent decision-making, having a personal opinion, being able to justify his decision, respecting the opinions of others, understanding their mistakes.
Keywords: competence; pedagogy; psychology; skill